The science book of electricity - Ardley, Neil. (San Diego : Harcourt Brace Jovanovich, 1991)
Simple experiments demonstrate basic principles of electricity.
"Gulliver books.".
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
4.5
4.5
Keywords: Electricity -- Juvenile literature; Electricity -- Experiments; Experiments; Electricity -- Experiments